2016
DOI: 10.1164/rccm.201507-1493oc
|View full text |Cite|
|
Sign up to set email alerts
|

The Early Development of Wheeze. Environmental Determinants and Genetic Susceptibility at 17q21

Abstract: RATIONALE: Growing up on a farm protects from childhood asthma and early wheeze. Virustriggered wheeze in infancy predicts asthma in individuals with a genetic asthma risk associated with chromosome 17q21. OBJECTIVES: To test environmental determinants of infections and wheeze in the first year of life, potential modifications of these associations by 17q21, and the implications for different trajectories of wheeze. METHODS: We followed 983 children in rural areas of Europe from birth until age 6 years. Sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 33 publications
(41 reference statements)
10
121
0
4
Order By: Relevance
“…Moreover, SNPs at this locus are robustly associated with childhood-onset asthma and asthma in children exposed to environmental tobacco smoke, with respiratory infections and hospitalizations, and with wheezing illnesses in early life [26,4448], but not with allergic phenotypes [26,37,45,49,50] (with two exceptions [51,52]). In fact, the risk for asthma associated with genotype at the 17q21 locus is confined to children who wheeze in early life: the 17q21 genotype is not associated with asthma among children who do not wheeze in early life [37,53]. Surprisingly, however, the 17q21 genotype is also associated with protection from wheezing in the first year of life and subsequent asthma among children exposed to barn animals [53].…”
Section: Asthma Genetics and The Farm Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SNPs at this locus are robustly associated with childhood-onset asthma and asthma in children exposed to environmental tobacco smoke, with respiratory infections and hospitalizations, and with wheezing illnesses in early life [26,4448], but not with allergic phenotypes [26,37,45,49,50] (with two exceptions [51,52]). In fact, the risk for asthma associated with genotype at the 17q21 locus is confined to children who wheeze in early life: the 17q21 genotype is not associated with asthma among children who do not wheeze in early life [37,53]. Surprisingly, however, the 17q21 genotype is also associated with protection from wheezing in the first year of life and subsequent asthma among children exposed to barn animals [53].…”
Section: Asthma Genetics and The Farm Effectmentioning
confidence: 99%
“…In fact, the risk for asthma associated with genotype at the 17q21 locus is confined to children who wheeze in early life: the 17q21 genotype is not associated with asthma among children who do not wheeze in early life [37,53]. Surprisingly, however, the 17q21 genotype is also associated with protection from wheezing in the first year of life and subsequent asthma among children exposed to barn animals [53]. While neither the specific 17q21 gene(s) involved in risk or protection nor the role of ORMDL3 or GSDMB in asthma pathogenesis is currently known, it is clear that this asthma locus modulates risk or protection associated with two of the most important environmental exposures associated with asthma: virus-induced wheezing illness in early life and exposure to farm animals.…”
Section: Asthma Genetics and The Farm Effectmentioning
confidence: 99%
“…What bacterial or host factors promote stability versus instability of the microbiome during RSV infection? Early-life environmental exposure such as living on a dairy farm reduces the risk of early-life viral illnesses, likely through a mechanism involving alterations to the microbiome (9). Is there a role for vitamin D, breastfeeding, mode of delivery, and perhaps the family dog in preventing more severe RSV infection (10,11)?…”
mentioning
confidence: 99%
“…The association of rs7216389 with exacerbation risk, bronchial responsiveness38 and also gene interactions with arginase1 (rs37756780, ARG1 )39 may be a potential underlying mechanism to explain the enrichment and depletion of SNP rs7216389 in clusters 3 and 4, respectively. Moreover, recently, a gene-by-environment interaction of locus 17q21 has been demonstrated 40. In particular, it has been shown that individuals carrying the GSDMB rs7216389 variant particularly benefit from growing up in a farming environment due to its protective effect against virus-induced wheeze and non-atopic asthma.…”
Section: Discussionmentioning
confidence: 99%